RANCANG BANGUN MESIN SENAI UNTUK ULIR M11 - Pujono Pujono; Istofa Rifqy Widya Fauzi (Infotekmesin, 2018)
Bolting machine is a machine which is designed to conduct the making process of outside thread without rotating the handlebar of workpiece using hand manually, Therefore, the machine can help the processing in some industries which do not have qualified operators. The purpose of the designing and calculating of machine elements on senai machineis to create a design and make it in real product that can create outside thread with the maximum size of M11, to calculate parts of machine elements, i.e. axis diameter and sprocket chain and to create the real machine product. The designing method used follows these steps, i.e. problem identification, initial idea, improvement of the idea, analysis of design, decision making, and implementation. The result of the evaluation on concept design was the cutter holder on the chuck variable and themover shaft handle. The result of machine elements calculation showed that the electric motor power was 40 watt, shaft diameter was 25 mm with inside diameter of 16 mm, the bearing used was 6205 Ball Bearing, and the thread capacity was M11 metric thread.